2017
DOI: 10.1111/ene.13468
|View full text |Cite
|
Sign up to set email alerts
|

Hypermetabolism is a deleterious prognostic factor in patients with amyotrophic lateral sclerosis

Abstract: Background and purpose: The aim of this study was to investigate patients with amyotrophic lateral sclerosis in order to determine their nutritional, neurological and respiratory parameters, and survival according to metabolic level. Methods: Nutritional assessment included resting energy expenditure (REE) measured by indirect calorimetry [hypermetabolism if REE variation (DREE) > 10%] and fat mass (FM) using impedancemetry. Neurological assessment included the Amyotrophic Lateral Sclerosis Functional Rating S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 28 publications
2
72
0
Order By: Relevance
“…In normal physiology, whole-body energy homeostasis serves to balance the supply of energy with the use of energy and is crucial for stable body weight. In ALS, several reports of hypermetabolism (18)(19)(20)(21)(22)(23)(24)(25) have suggested that increased whole-body energy expenditure is a principal cause for weight loss. However, no study has conclusively shown that weight loss in ALS is a consequence of hypermetabolism.…”
Section: Introductionmentioning
confidence: 99%
“…In normal physiology, whole-body energy homeostasis serves to balance the supply of energy with the use of energy and is crucial for stable body weight. In ALS, several reports of hypermetabolism (18)(19)(20)(21)(22)(23)(24)(25) have suggested that increased whole-body energy expenditure is a principal cause for weight loss. However, no study has conclusively shown that weight loss in ALS is a consequence of hypermetabolism.…”
Section: Introductionmentioning
confidence: 99%
“…In the current issue of the journal, Jesus et al . addressed the importance of hypermetabolism as an adverse prognostic biomarker in a large ALS cohort. The study re‐affirmed that hypermetabolism was evident in approximately 50% of ALS patients, with three prognostic groups identified based on the REE variation values (<10%, 10%–20% and >20%).…”
mentioning
confidence: 99%
“…In the current issue of the journal, Jesus et al [5] addressed the importance of hypermetabolism as an adverse prognostic biomarker in a large ALS cohort.…”
mentioning
confidence: 99%
“…Overall, hypermetabolism is a feature of more than half of the ALS population and was recently shown to be a deleterious prognostic factor. Patients with hypermetabolism have a 20% worse prognosis than those that do not exhibit the hypermetabolism phenotype 30,31 . Until now, hypermetabolism in ALS has mostly been considered in relation to glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%